Rise of the African Novel In English: a Study of Chinua Achebi’S Novels: Exploring Realistic Portrayal and Sociopolitical Commentary in Chinua Achebe's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Chinua Achebe has proven his worth among English-speakingAfrican novelists by representing the African social and political environmentin a thoroughly realistic way. His novels depict life within a particularhistorical background, and convey a sense of growing disgust and unrest withinNigerian society, a society that has started to emerge from the ‘colonialcomplex’ caused by years of denigration and self-abasement. A Man of the People (1967) isAchebe’s fourth novel. It describes Nigeria in its post-independence phase,during which time the country became a ‘cesspool of corruption and misrule’ inthe context of colonial-style social and economic development, a situation thatresulted in conflict between the emergent, elitist middle class and the generalpopulation. Achebe’s reputation as a novelist rests on his impartial understandingof, and ability to represent, the Nigerian environment. His realisticcharacterization, and diagnosis, of his country’s malaise has the power toinspire a revolution informed by African ideologies.